2016
DOI: 10.1289/ehp.1409671
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Causal Effects of Long-Term PM 2.5 Exposure on Mortality in New Jersey

Abstract: Background:Many studies have reported the associations between long-term exposure to PM2.5 and increased risk of death. However, to our knowledge, none has used a causal modeling approach or controlled for long-term temperature exposure, and few have used a general population sample.Objective:We estimated the causal effects of long-term PM2.5 exposure on mortality and tested the effect modifications by seasonal temperatures, census tract–level socioeconomic variables, and county-level health conditions.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
111
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(113 citation statements)
references
References 32 publications
2
111
0
Order By: Relevance
“…11 A study in New Jersey also estimated that the effect increased with the percentage of black residents in each census tract. 32 However, they did not analyze race on an individual level and instead used the percentage of black residents as an ecologic surrogate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 A study in New Jersey also estimated that the effect increased with the percentage of black residents in each census tract. 32 However, they did not analyze race on an individual level and instead used the percentage of black residents as an ecologic surrogate.…”
Section: Discussionmentioning
confidence: 99%
“…11 Consistently, a recent study in New Jersey also found that the risks are higher among individuals living in a census tract with lower median income. 32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we found that our results were consistent with others published in the literature (Section 6 in the Supplementary Appendix). 5,17,[24][25][26][27][28] There was a significant association between PM 2.5 exposure and mortality when the analysis was restricted to concentrations below 12 μg per cubic meter, with a steeper slope below that level. This association indicated that the health-benefit-per-unit decrease in the concentration of PM 2.5 is larger for PM 2.5 concentrations that are below the current annual NAAQS than the health benefit of decreases in PM 2.5 concentrations that are above that level.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Studies suggest that fine particles (particles with a mass median aerodynamic diameter of less than 2.5 μm [PM 2.5 ]) are a public health concern, 3 with exposure linked to decreased life expectancy. [4][5][6] Long-term exposure to ozone has also been associated with reduced survival in several recent studies, although evidence is sparse. 4,[7][8][9] Studies with large cohorts have investigated the relationship between long-term exposures to PM 2.5 and ozone and mortality 4,[9][10][11][12][13] ; others have estimated the health effects of fine particles at low concentrations (e.g., below 12 μg per cubic meter for PM 2.5 ).…”
mentioning
confidence: 99%